New species of Philygria Stenhammar (Diptera: Ephydridae) from Germany - Stuke, Jens-Hermann (Zootaxa, 2021)
Philygria doczkali spec. nov. is described from Zugspitze (Wetterstein Mountains, Germany) in the Bavarian Alps and Philygria dispar spec. nov. is described from southern Lower Saxony (Germany).